Analysis of the Impact of Clean Coal Technologies on the Share of Coal in Poland’s Energy Mix - Aurelia Rybak; Aleksandra Rybak; Jarosław Joostberens; Joachim Pielot; Piotr Toś (Energies, 2024)
This article presents research results on the share of coal in the energy mix and the impact of clean coal technologies on Poland’s energy mix. Two mathematical models were utilised: the Boltzmann sigmoidal curve and a supervised machine learning model that employs multiple regressions. Eight explanatory variables were incorporated into the model, the influence of which on the explained variable was confirmed by Student’s t-test. The constructed models were verified using ex post errors and the Durbin–Watson and Shapiro–Wilk statistical tests. It was observed that the share of coal in the mix decreased more dynamically after 2015 compared to previous years. Furthermore, a simulation was conducted using the machine learning model, which confirmed the hypothesis on the influence of clean coal technologies on the level of coal share in the Poland energy production structure. As shown by the analysis and simulation, coal could be maintained in the energy mixes of EU countries, and even if the negative aspects of using this fuel were limited—primarily the emission of harmful substances—its share could even increase. It was noted that this share could be higher by 22% assuming a return to the interest in CCT levels from before 2015 and the reduction in CO2 emissions using membrane techniques proposed by the authors. Clean coal technologies would enable diversification of the energy mix, which is an important aspect of energy security. They would also enable the gradual introduction of renewable energy sources or other energy sources, which would facilitate the transition stage on the way to a sustainable energy mix.